Properties of Kenaf (Hibiscus Cannabinus L.) Bast Fibre Reinforced Unsaturated Polyester Composite - Aw Yeong, Chee Hong (2004)
The main purpose of this research is to exploit new bio-fibre resources for the structural composite industries. Kenaf bast fibre was combined with thermosetting resin matrix to produce advance composites and its mechanical and dimensional stability properties were investigated. Unsaturated polyester was used as matrix resin in this project which consist 44-48% of styrene monomer and form gel in 24-30 minutes with 1% methyl ethyl ketone peroxide.